EFEKTIFITAS KOMBINASI HYPNOBREASTFEEDING DAN KONSUMSI BLUSTRU TERHADAP OPTIMALISASI PRODUKSI KOLOSTRUM PADA IBU POSTPARTUM DI RUMAH SAKIT Dr. SOEBANDI JEMBER - Asmuji**, Diyan Indriyani* (The Indonesian Journal of Health Science, 2016)
Colostrum is the mother's milk (ASI), which came out at the end of the period of pregnancy until 3-4 days after birth, the color is slightly yellowish. Colostrum is important for a newborn because it is a source of major nutrients. However, with regard to the production of colostrum, which is part of the ASI still found difficulties in optimalisasinya. This research was conducted in RSD Dr. Soebandi Jember began on March 28 to May 31, 2016.. Statistical test using Independent T-Test, with a significance level (?) = 5% (0.05) The results shows that the production of colostrum in mothers postpartum in RSD. Dr. Soebandi Jember conducted hypnobreastfeeding combination action and consumption blustru obtained a mean value of 21.93 with a minimum value of 15 and a maximum value of 26, while no intervention mean value 15.07 with a minimum value of 13 and a maximum value of 24. The combination hypnobreastfeeding and effective blustru consumption to optimize the production of colostrum at postpartum mothers in RSD. Dr. Soebandi Jember with P Value 0.00. It is recommended for health care workers to conduct hypnobreastfeeding maternal postpartum maternal postpartum and recommends consuming blustru to optimize milk production. Keywords : Hypnobreastfeeding , Blustru , Production Colostrum